The Effects of Reforming a Federal Employment Agency on Labor Demand - Kornelius Kraft; Alexander Lammers (Institute of Labor Economics (IZA), 2021)
In this paper we report the results of an empirical study on the employment growth effects of a policy intervention, explicitly aimed at increasing placement efficiency of the Federal Employment Agency in Germany. We use the Hartz III reform in the year 2004 as an exogenous intervention that improves the matching process and compare establishments that use the services of the Federal Employment Agency with establishments that do not use the placement services. Using detailed German establishment level data, our difference-in-differences estimates reveal an increase in employment growth among those firms that use the agency for their recruitment activities compared to non-user firms. After the Hartz III reform was in place, establishments using the agency grew roughly two percentage points faster in terms of employment relative to non-users and those establishments achieve an increase in the proportion of hires. We provide several robustness tests using, for example, inverse-probability weighting to additionally account for differences in observable characteristics. Our paper highlights the importance of the placement service on the labor demand side, in particular on the so far overlooked establishment level.
Keywords: J23; J64; J68; 330; Hartz III reform; Federal Employment Agency; matching efficiency; employment growth; difference-in-differences